2014
DOI: 10.1080/13607863.2013.875122
|View full text |Cite
|
Sign up to set email alerts
|

Reducing loneliness amongst older people: a systematic search and narrative review

Abstract: Further research into interventions using new technologies to reduce loneliness in older people is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
166
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(181 citation statements)
references
References 61 publications
6
166
3
6
Order By: Relevance
“…The problem of dementia and cognitive decline in China, therefore, may be exacerbated by their association with loneliness. Systematic reviews suggest that loneliness can be reduced with certain interventions, particularly those that address maladaptive social cognition 42, 43 . Hence, from the perspective of public health, the disease burden of dementia in China could be reduced through effective interventions aimed at preventing/reducing loneliness, especially chronic loneliness.…”
Section: Resultsmentioning
confidence: 99%
“…The problem of dementia and cognitive decline in China, therefore, may be exacerbated by their association with loneliness. Systematic reviews suggest that loneliness can be reduced with certain interventions, particularly those that address maladaptive social cognition 42, 43 . Hence, from the perspective of public health, the disease burden of dementia in China could be reduced through effective interventions aimed at preventing/reducing loneliness, especially chronic loneliness.…”
Section: Resultsmentioning
confidence: 99%
“…No Aotearoa/New Zealand studies were found that tested the effectiveness of community‐based group programs, or individual telephone, mentoring or letter companion services aimed at ameliorating older adults’ loneliness. A systematic search of intervention research reported in 2014 found loneliness was significantly reduced in one, of nine, community‐based group intervention studies, one, of three, one‐to‐one mentoring studies, and three, of six, studies using new technologies including web‐based interventions and computer games 46. These results suggest that one‐to‐one interventions may be more likely to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Increased physical activity appears to be protective against loneliness; however, few interventions have incorporated elements of physical activity programs (Dahlberg & McKee, 2014; Hawkley et al, 2009; Luo et al, 2012). Various technologies (e.g., computers, tablets) have been used in research studies with promise (Hagan, Manktelow, Taylor, & Mallett, 2014), but costs and limited exposure to these technologies among older adults have limited their acceptance.…”
Section: Discussionmentioning
confidence: 99%